Supply chain lead time reduction in a pharmaceutical production warehouse – a case study - Ahmed Zainul, Abideen; Fazeeda, Mohamad (Amerald, 2019)
Purpose The purpose of this study is to apply value stream mapping (VSM) in Malaysian pharmaceutical production warehouse. A current and future state value stream map from the raw material receiving end to the production unit was developed to find out waste and unwanted lead time. It was very much essential to cut down the supply chain lead time at the initial phase as the raw material unloading, sorting, temporary storage and dispatch to production were seen contributing to a huge lead time build-up.